Comparison of qualitative and quantitative fit-testing results for three commonly used respirators in the healthcare sector. Issue 3 (4th March 2017) - Hon, Chun-Yip; Danyluk, Quinn; Bryce, Elizabeth; Janssen, Bob; Neudorf, Mike; Yassi, Annalee; Shen, Hui; Astrakianakis, George
ABSTRACT: N95 filtering facepiece respirators are used by healthcare workers when there is a risk of exposure to airborne hazards during aerosol-generating procedures. Respirator fit-testing is required prior to use to ensure that the selected respirator provides an adequate face seal. Two common fit-test methods can be employed: qualitative fit-test (QLFT) or quantitative fit-test (QNFT). Respiratory protection standards deem both fit-tests to be acceptable. However, previous studies have indicated that fit-test results may differ between QLFT and QNFT and that the outcomes may also be influenced by the type of respirator model. The aim of this study was to determine if there is a difference in fit-test outcomes with our suite of respirators, 3M - 1860S, 1860, AND 1870, and whether the model impacts the fit-test results. Subjects were recruited from residential care facilities. Each participant was assigned a respirator and underwent sequential QLFT and QNFT fit-tests and the results (either pass or fail) were recorded. To ascertain the degree of agreement between the two fit-tests, a Kappa (Κ) statistic was conducted as per the American National Standards Institute (ANSI) respiratory protection standard. The pass-fail rates were stratified by respirator model and a Kappa statistic was calculated for each to determine effect of model on fit-test outcomes. We had 619 participants and the aggregate Κ statistic for all respirators was 0.63 which is below the suggested ANSI threshold of 0.70. There was no statistically significant difference in results when stratified by respirator model. QNFT and QLFT produced different fit-test outcomes for the three respirator models examined. The disagreement in outcomes between the two fit-test methods with our suite of N95 filtering facepiece respirators was approximately 12%. Our findings may benefit other healthcare organizations that use these three respirators.